2009
DOI: 10.1007/s11816-009-0123-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Indica rice OsBADH1 gene under salinity stress in transgenic tobacco

Abstract: Glycine betaine has been reported as an osmoprotectant compound conferring tolerance to salinity and osmotic stresses in plants. We previously found that the expression of betaine aldehyde dehydrogenase 1 gene (OsBADH1), encoding a key enzyme for glycine betaine biosynthesis pathway, showed close correlation with salt tolerance of rice. In this study, the expression of the OsBADH1 gene in transgenic tobacco was investigated in response to salt stress using a transgenic approach. Transgenic tobacco plants expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…However, there was a 10-fold (0.15-0.25 lmol g -1 FW) increase in the GB levels when salt stress was imposed. Although the preliminary experiment in transgenic tobacco showed higher amounts of GB accumulation (0.14-0.56 lmol g -1 FW; Hasthanasombut et al 2010), it has been shown that the maize ubiquitin promoter induces stronger gene expression in monocots than in dicots (McElroy and Brettell 1994), therefore, this result suggests that the Indica OsBADH1 mRNA was also partially degraded in transgenic Japonica rice.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, there was a 10-fold (0.15-0.25 lmol g -1 FW) increase in the GB levels when salt stress was imposed. Although the preliminary experiment in transgenic tobacco showed higher amounts of GB accumulation (0.14-0.56 lmol g -1 FW; Hasthanasombut et al 2010), it has been shown that the maize ubiquitin promoter induces stronger gene expression in monocots than in dicots (McElroy and Brettell 1994), therefore, this result suggests that the Indica OsBADH1 mRNA was also partially degraded in transgenic Japonica rice.…”
Section: Discussionmentioning
confidence: 87%
“…Then, the XbaI-XhoI fragment from pET29 was linked between the promoter of the maize ubiquitin 1 gene and the terminator of the nopaline synthase (nos) gene in pSub221s plasmid. Agrobacterium strain EHA101 harboring binary plasmid vector (pEKH2/ Ubi::OsBADH1) was constructed as described previously (Hasthanasombut et al 2010).…”
Section: Production Of Transgenic Osbadh1 Rice and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our transgenic plants possibly also accumulated GABA and gained improved salt stress tolerance, since GABA can function as an osmoprotectant in plants (Mazzucotelli et al 2006). Most recently, transgenic tobacco (Nicotiana tabacum L.) plants expressing OsBADH1 from indica rice showed improved salt stress tolerance (Hasthanasombut et al 2010). Those plants might also accumulate GABA, although no data have been presented in the literature.…”
Section: Discussionmentioning
confidence: 89%